Constructing a three-dimensional nano-crystalline diamond network within polymer composites for enhanced thermal conductivity. Issue 44 (4th November 2021) - Xiong, Shaoyang; Qin, Yue; Li, Linhong; Yang, Guoyong; Li, Maohua; Wei, Xianzhe; Song, Guichen; Man, Weidong; Wang, Bo; Cai, Tao; Yi, Jian; Fu, Li; et al.
Abstract : A facile and scalable method is developed to construct a three-dimensional porous diamond framework toward the high thermal conductivity of epoxy composites. Abstract : In order to meet the requirement of thermal performance with the rapid development of high-performance electronic devices, constructing a three-dimensional thermal transport skeleton is an effective method for enhancing the thermal conductivity of polymer composites. In this work, a three-dimensional porous diamond framework was prepared by depositing nano-crystalline diamond on alumina foam which was impregnated with epoxy to obtain a nano-crystalline diamond@alumina foam/epoxy composite. The epoxy composite with nano-crystalline diamond@alumina foam demonstrated a thermal conductivity of 2.21 W m −1 K −1, which was increased by 1063% in comparison with pure epoxy. The thermal conductivity of the epoxy composite measured under various conditions and heat transport applications demonstrates that it possesses excellent thermal transportation and stability properties. This work provides a new idea to significantly enhance the thermal transportation properties of epoxy composites in the application of advanced packaging materials.